The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1016/j.jvs.2008.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Compression therapy in breast cancer-related lymphedema: A randomized, controlled comparative study of relation between volume and interface pressure changes

Abstract: Inelastic, multi-layer, multi-component compression bandages with lower pressure (20-30 mm Hg) are better tolerated and achieve the same amount of arm volume reduction as bandages applied with higher pressure (44-58 mm Hg) in the first 24 hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 20 publications
3
74
0
6
Order By: Relevance
“…Previous research has showed that the subgarment pressure used often is higher than needed for sufficient treatment. 3 A method for measuring subgarment pressure in vivo, and for determining at which pressure the treatment effect is optimal, is essential to ameliorate the treatment of lymphedema.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has showed that the subgarment pressure used often is higher than needed for sufficient treatment. 3 A method for measuring subgarment pressure in vivo, and for determining at which pressure the treatment effect is optimal, is essential to ameliorate the treatment of lymphedema.…”
Section: Resultsmentioning
confidence: 99%
“…Compliance is essential to maintain the compression therapy and hence a stable arm volume postoperatively. 3 The aims of the present study were to establish a method of measuring subgarment pressure using the I-scan Ò (Tekscan Inc.) pressure measuring equipment and to analyze initial and post-wear and tear subgarment pressure along the extremity of 5 similar compression garments from three different manufacturers.…”
Section: Lymphatic Research and Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…Bandages changed daily should not be applied with the same high pressure compared to bandages changed once or twice weekly. The optimal pressure range for reducing edema, corresponding to a pressure range around 30 mm Hg for the upper and 50-60 mm Hg for the lower extremity [1,2,6]. Higher pressures may be counterproductive.…”
Section: Discussionmentioning
confidence: 99%
“…Compression mechanisms are one of the main forms of therapy to reduce the volume of edema. A study comparing multicomponent and twocomponent inelastic bandages reported good results using multicomponent bandaging (Damstra et al 2009;Kang et al 2012). However, the twocomponent system is considered a suitable alternative (Lamprou et al 2011).…”
Section: Introductionmentioning
confidence: 99%